2014
DOI: 10.1371/journal.pone.0103386
|View full text |Cite
|
Sign up to set email alerts
|

Sociosexual and Communication Deficits after Traumatic Injury to the Developing Murine Brain

Abstract: Despite the life-long implications of social and communication dysfunction after pediatric traumatic brain injury, there is a poor understanding of these deficits in terms of their developmental trajectory and underlying mechanisms. In a well-characterized murine model of pediatric brain injury, we recently demonstrated that pronounced deficits in social interactions emerge across maturation to adulthood after injury at postnatal day (p) 21, approximating a toddler-aged child. Extending these findings, we here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 132 publications
(219 reference statements)
1
25
0
Order By: Relevance
“…2,74,89,93,106 In a small subset of CCI rats, a protuberance similar to a leptomeningeal cyst formed several days after injury, and MRI showed findings similar to those in human infants with a leptomeningeal cyst. 82 In P11 CCI, similar deformation of the lateral ventricle has been noted on histological analyses.…”
Section: Discussionmentioning
confidence: 80%
“…2,74,89,93,106 In a small subset of CCI rats, a protuberance similar to a leptomeningeal cyst formed several days after injury, and MRI showed findings similar to those in human infants with a leptomeningeal cyst. 82 In P11 CCI, similar deformation of the lateral ventricle has been noted on histological analyses.…”
Section: Discussionmentioning
confidence: 80%
“…Across a range of injury models including FPI, CCI, impact acceleration, blast and repetitive closed skull impacts of varying severity, investigators have reported either a reduction in social investigation and social recognition after TBI (Bajwa et al, 2016; Fenn et al, 2013; Klemenhagen et al, 2013; Koliatsos et al, 2011; Pandey et al, 2009; Semple et al, 2012; Semple et al, 2014), or the lack of a difference compared to sham-operated controls (Patel et al, 2014; Shultz et al, 2012; Shultz et al, 2011). Further studies are needed to validate the incorporation of specific social tasks in this context, as the characterization of social outcomes across a range of TBI models will likely enhance our understanding of the complex interaction between neuropathology and functional outcomes.…”
Section: Identifying Social Behavior Impairments In Brain-injured mentioning
confidence: 99%
“…Further, at adulthood, TBI mice were more likely to exert social dominance in the tube task compared to sham-operated controls (Semple et al, 2012). Brain-injured mice also present with aberrant social communication, as evidenced by a striking reduction in scent marking behavior at adulthood after pTBI, and abnormal context-dependent ultrasonic vocalizations in response to female stimuli (Semple et al, 2014). Together, these findings reveal an emergence of aberrant social behavior over time after early-life injury, a trajectory that parallels the development of cognitive deficits in this model, as well as social dysfunction reported many years after childhood TBI in patients.…”
Section: Identifying Social Behavior Impairments In Brain-injured mentioning
confidence: 99%
“…To address the extent to which the age at injury influences social behaviors, a subsequent study from the same investigators recently compared mice injured at PND 21 or PND 35 (Semple et al, 2014). Mice injured at a young postnatal age (PND 21), when tested at adulthood, exhibited reduced scent marking behavior and an alteration in context-dependent USVs in response to female stimuli.…”
Section: Social Behavior After Injury To the Developing Brainmentioning
confidence: 99%
“…Changes in the corpus callosum in terms of volumetric atrophy, microstructural integrity or connectivity (Ewing-Cobbs et al, 2008; Wu et al, 2010; Ewing-Cobbs et al, 2012; Semple et al, 2014) have been associated with poorer social outcomes in both adults and children after TBI (Beauchamp et al, 2009; Ryan et al, 2013). In children, volumetric changes of both grey and white matter structures after injury are likely to reflect not only ongoing neurodegeneration, but also result from the retardation of normal growth trajectories.…”
Section: Social Behavior After Injury To the Developing Brainmentioning
confidence: 99%